Comparative proteome analysis of cryopreserved flagella and head plasma membrane proteins from sea bream spermatozoa: effect of antifreeze proteins. - Loredana Zilli (Public Library of Science (PLoS), 2014)
Cryopreservation induces injuries to fish spermatozoa that in turn affect sperm quality in terms of fertilization ability, motility, DNA and protein integrity and larval survival. To reduce the loss of sperm quality due to freezing-thawing, it is necessary to improve these procedures. In the present study we investigated the ability of two antifreeze proteins (AFPI and AFPIII) to reduce the loss of quality of sea bream spermatozoa due to cryopreservation. To do so, we compared viability, motility, straight-line velocity and curvilinear velocity of fresh and (AFPs)-cryopreserved spermatozoa. AFPIII addition to cryopreservation medium improved viability, motility and straight-line velocity with respect to DMSO or DMSO plus AFPI. To clarify the molecular mechanism(s) underlying these findings, the protein profile of two different cryopreserved sperm domains, flagella and head plasma membranes, was analysed. The protein profiles differed between fresh and frozen-thawed semen and results of the image analysis demonstrated that, after cryopreservation, out of 270 proteins 12 were decreased and 7 were increased in isolated flagella, and out of 150 proteins 6 showed a significant decrease and 4 showed a significant increase in head membranes. Mass spectrometry analysis identified 6 proteins (4 from isolated flagella and 2 present both in flagella and head plasma membranes) within the protein spots affected by the freezing-thawing procedure. 3 out of 4 proteins from isolated flagella were involved in the sperm bioenergetic system. Our results indicate that the ability of AFPIII to protect sea bream sperm quality can be, at least in part, ascribed to reducing changes in the sperm protein profile occurring during the freezing-thawing procedure. Our results clearly demonstrated that AFPIII addition to cryopreservation medium improved the protection against freezing respect to DMSO or DMSO plus AFPI. In addition we propose specific proteins of spermatozoa as markers related to the procedures of fish sperm cryopreservation.